THE IMPLEMENTATION OF CHARACTER EDUCATION ON PERSONALITY DEVELOPMENT THROUGH HABITUATION METHOD IN MADRASAH - Windiasari, Kikik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The Diniyah Madrasah Fathimatuzzahro' institution applies the habituation method to the formation of students' personalities. Through the habituation policy, it is expected to be able to form smart, independent and quality student characters. Researchers conducted research with the aim of describing the implementation of convergence theory on the development of students in Madrasah Diniyah Fathimatuzzahro'. This research includes field research using a qualitative approach. Data collection techniques using interview, observation and documentation methods. And the techniques chosen in data analysis are data reduction, data display and data verification to draw conclusions from the data collected. From the results of the study it can be concluded that with the habituation carried out by madrasah educational institutions to build the development of students' personalities through the habituation of reading juz 'amma and nadhom which is carried out before teaching and learning activities take place.